If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -23 = 7w Solving -23 = 7w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-7w' to each side of the equation. -23 + -7w = 7w + -7w Combine like terms: 7w + -7w = 0 -23 + -7w = 0 Add '23' to each side of the equation. -23 + 23 + -7w = 0 + 23 Combine like terms: -23 + 23 = 0 0 + -7w = 0 + 23 -7w = 0 + 23 Combine like terms: 0 + 23 = 23 -7w = 23 Divide each side by '-7'. w = -3.285714286 Simplifying w = -3.285714286
| 4a-3a-1=13 | | x=-3+15+5 | | -23=-7w | | -24s=8 | | 19-2d=7 | | 3(N-12)=27 | | -10y+2+3y+8y=4 | | 6.4=-0.4x^2+10 | | 7(w+1)=9w+11 | | d/-2=2 | | -(y+5)+2y-11=-26 | | 4w+48=-2(w-9) | | -10.5-9.7=2w+1.4-1w | | 3(x+8)=63 | | 5p-4p+2p+3=12 | | 9^3X-1=1/27 | | 8t=-8 | | x^3+x=500 | | -10h=-20 | | 2/12=6/x | | 15w+-19w=-16 | | W/2-3^12 | | tg(-x)=1-2tg(x) | | cos(240)= | | x(13+x)=0 | | (3-i)(x-iy)=3-11i | | x+y=1.70 | | 12(x-4)-8(2x-7)=3(x+5) | | 3+10x=0.5 | | 7(v-4)=3v-4 | | 11x-54-8x-12=7x+30-6x | | 5u-43=9(u-7) |